REALITAS MASYARAKAT DALAM MEDIA - Ronda, Mirza (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2006)
As a journalist, the objectivities and neutralist is a crucial thing to hold when they do their journalism  tasks.  Its seems an impossible thing to do.  In fact, News or other journalisms products are not a reality. They just pieces of reality (Media  Image)  which is produced by an influenced and distorted product.